Cork as a new (green) coating for solid-phase microextraction: Determination of polycyclic aromatic hydrocarbons in water samples by gas chromatography–mass spectrometry - Dias, Adriana Neves; Simão, Vanessa; Merib, Josias; Carasek, Eduardo (Analytica Chimica Acta, 2013)
A new fiber for solid-phase microextraction (SPME) was prepared employing cork as a coating. The morphology and composition of the cork fiber was evaluated by scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR), respectively. The proposed fiber was used for the determination of polycyclic aromatic hydrocarbons (PAHs) in river water samples by gas chromatography–selected ion monitoring–mass spectrometry (GC–SIM–MS). A central composite design was used for optimization of the variables involved in the extraction of PAHs from water samples. The optimal extraction conditions were extraction time and temperature of 60 min and 80 °C, respectively. The detection and quantification limits were 0.03 and 0.1 μg L−1, respectively. The recovery values were between 70.2 and 103.2% and the RSD was ≤15.7 (n = 3). The linear range was 0.1–10 μg L−1 with r ≥ 0.96 and the fiber-to-fiber reproducibility showed RSD ≤ 18.6% (n = 5). The efficiency of the cork fiber was compared with commercially available fibers and good results were achieved, demonstrating the applicability and great potential of cork as a coating for SPME.
Keywords: Cork; GC–MS; PAHs; Solid-phase microextraction; Water samples

Improved biomonitoring of airborne contaminants by combined use of holm oak leaves and epiphytic moss - De Nicola, F.; Spagnuolo, V.; Baldantoni, D.; Sessa, L.; Alfani, A.; Bargagli, R.; Monaci, F.; Terracciano, S.; Giordano, S. (CHEMOSPHERE, 2013)
Concentrations of 12 elements (Ca, Cd, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb and Zn) and 16 EPA-listed PAHs were detected in Quercus ilex leaves and the epiphytic moss Leptodon smithii collected at urban, periurban and extraurban holm oak stands, in two Italian Regions (Campania and Tuscany). Levels of environmental contaminants were generally higher in leaves and moss from urban areas than periurban and extraurban ones and samples from Campania had the highest PAH content. The epiphytic moss accumulated higher concentrations of trace elements than leaves and the latter showed a higher accumulation capability for PAHs, especially for those with low molecular weight. The different bioaccumulation in leaves and moss were explained in terms of their distinctive morphological and ecophysiological characteristics. The combined approach seems a promising tool for the monitoring of a wide range of pollutants in Mediterranean urban and extraurban environments. (C) 2013 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: Air pollution gradient; Bioaccumulation; Leptodon smithii; PAHs; Quercus ilex; Trace Elements

A multi-approach monitoring of particulate matter, metals and PAHs in an urban street canyon - De Nicola, Flavia; Murena, Fabio; Costagliola, M. Antonietta; Alfani, Anna; Baldantoni, Daniela; Prati, M. Vittoria; Sessa, Ludovica; Spagnuolo, Valeria; Giordano, Simonetta (ENVIRONMENTAL SCIENCE AND POLLUTION RESEARCH, 2013)
For the first time until now, the results from a prediction model (Atmospheric Dispersion Modelling System (ADMS)-Road) of pollutant dispersion in a street canyon were compared to the results obtained from biomonitors. In particular, the instrumental monitoring of particulate matter (PM10) and the biomonitoring of 14 polycyclic aromatic hydrocarbons (PAHs) and 11 metals by Quercus ilex leaves and Hypnum cupressiforme moss bags, acting as long- and short-term accumulators, respectively, were carried out. For both PAHs and metals, similar bioaccumulation trends were observed, with higher concentrations in biomonitors exposed at the leeward canyon side, affected by primary air vortex. The major pollutant accumulation at the leeward side was also predicted by the ADMS-Road model, on the basis of the prevailing wind direction that determines different exposure of the street canyon sides to pollutants emitted by vehicular traffic. A clear vertical (3, 6 and 9 m) distribution gradient of pollutants was not observed, so that both the model and biomonitoring results suggested that local air turbulences in the street canyon could contribute to uniform pollutant distribution at different heights.
The following values have no corresponding Zotero field: pub-location: TIERGARTENSTRASSE 17, D-69121 HEIDELBERG, GERMANY publisher: SPRINGER HEIDELBERG
Keywords: Holm oak leaves; metals; Moss bags; Naples urban area; PAHs; Pollutant dispersion model

Role of Chemical Components of cork on Sorption of Aqueous Polycyclic Aromatic Hydrocarbons - Environ, J. (International Journal of Environmental Research, 2013)
In order to know the environmental behaviour of toxic pollutants it is fundamental to understand the role of chemical components of a material on sorption of such pollutants.In this study, the sorption of a mix of polycyclic aromatic hydrocarbons (PAHs) by cork fractions (i.e. raw cork (CF), free extractive cork (FEF) and nonsaponifiable (DESF)) has been investigated to better understand the role of biopolymers and extractable fraction of cork on their sorption behaviour. All samples were analyzed through elemental analysis and were examined using Fourier transform infrared spectroscopy. After removing the extractable fraction and the suberin from the cork, the sorption capacities (Koc ) of FEF and DESF exhibited mean reductions of 70% and 30% respectively. In addition, the sorption results of three pairs of cork samples with different chemical content confirm that the extractable fraction serves as the major sorption medium for PAHs. Considering only low molecular weight PAHs positive correlations between Koc with Kow (R2 =0.70) and F number (R2 =0.65) were found, showing that these parameters are involved in this adsorption process
Keywords: biopolymers; Cork; extractable fraction; organic pollutants; PAHs

A step towards the use of biomonitors as estimators of atmospheric PAHs for regulatory purposes. - Augusto, Sofia; Pereira, Maria J.; Máguas, Cristina; Branquinho, Cristina (Chemosphere, 2013)
One of the main drawbacks of using lichens to monitor atmospheric PAHs has been reported as the inexistence of studies aiming to translate PAH values in lichens into the atmospheric equivalents ones, in order to use this information for regulatory purposes. In this work, PAH concentrations in lichens were compared with PAH concentrations measured in a conventional active sampler in an outdoor environment for a 9-month span. Significant positive correlations between HMW-PAHs, Σ16 EPA-PAHs, and BaP equivalent concentrations in lichens and those in air (TSP) were found. Concentrations of Σ16 EPA-PAHs in lichens and air showed a seasonal variation, with highest values during winter and lowest values during summer. Meteorological variables - temperature, atmospheric pressure, relative humidity, and wind speed - showed to significantly influence PAH concentrations in both lichens and air. Based on the significant linear correlations, equations for translating PAH concentrations measured in lichens into equivalent ones for air were proposed for the first time, allowing a broader use of lichens' information regarding PAHs in monitoring schemes and decision-making.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 23668962
Keywords: Air; BaP; Biomonitors; Environment; Human health; PAHs

An integrated approach to understanding the sorption mechanism of phenanthrene by cork. - Olivella, M. À; Jové, P.; Bianchi, A.; Bazzicalupi, C.; Cano, L. (Chemosphere, 2012)
Previous studies have shown the high sorption affinity of polycyclic aromatic hydrocarbons by cork. The aim of the present work is to go further by investigating the sorption mechanism of polycyclic aromatic hydrocarbons (exemplified by phenanthrene) on cork and the availability of the chemical components (i.e. lignin, suberin, holocellulose and extractives) to retain phenanthrene. Two approaches were integrated to reach this objective: (1) statistical multivariate analysis to obtain correlations between the sorption capacity, measured as K(oc), and the sorbent properties (i.e. polarity, acidic functional groups, %dichloromethane extractives, %ethanol and water extractives, %suberin, %lignin and %holocellulose) and (2) modeling calculations to obtain information on interaction at the molecular level. The statistical multivariate analysis demonstrated a strong and positive correlation between K(oc) and the lignin content as well as negative correlations between K(oc) and the phenolic groups and %dichloromethane extractives contents. The modeling study showed that the lignin-phenanthrene interaction is mostly hydrophobic in nature being largely determined by the π-stacking interaction between the aromatic groups of the interacting partners. This result justifies the observed correlations as dichloromethane extractives, being hydrophobic, compete with phenanthrene adsorption, whereas phenolic groups, as well as negatively charged groups, enhance the hydrophilic character of the sorbent surface, thus hindering the adsorption of phenanthrene.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 23149185
Keywords: Biopolymer; Biosorption; Lignin; PAHs; p–p Interactions; suberin

Trace metals, peroxidase activity, PAHs contents and ecophysiological changes in Quercus ilex leaves in the urban area of Caserta (Italy). - Papa, S; Bartoli, G; Nacca, F; D'Abrosca, B; Cembrola, E; Pellegrino, a; Fiorentino, a; Fuggi, A; Fioretto, a (Journal of environmental management, 2012)
Trace metals and polycyclic aromatic hydrocarbons, severely affecting human, animal and plants health, highly contribute to the air pollution in urban areas mainly due to car traffic. In this study the air biomonitoring of the city of Caserta (South Italy) has been performed by using Quercus ilex L., a widespread ornamental plant in parks, gardens and avenues. The plant leaves from different sites within the urban area were collected and used to determine the concentrations of V, Cd, Cr, Pb, Ni, Cu, and PAHs as well as the free amino acid content and peroxidase enzyme activity as indices of the leaf physiological conditions. All the tested trace metals showed concentrations higher than the control site. Lead was positively correlated to Cd and Cr and showed, also, a positive trend with Ni and Cu that, in their turn, were highly correlated between them. Positive and significant correlations were evidenced between total PAHs and carcinogenic PAHs and negative correlations between those and all trace metals assayed except V. Cu and Cd contents evidence negative correlations with peroxidase activity, and the free amino acid contents. The PAHs, in particular Carc-PAHs, were negatively correlated to the tested heavy metals. POD was positively correlated only with V and negatively correlated with Cu and Cd.
Keywords: Amino acid contents; PAHs; peroxidase; Quercus ilex leaves; Trace Elements; Urban area

The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna (Journal of Environmental Science and Health, Part A, 2011)
The aim of this study is to determine the sorption-desorption behavior of a mixture of thirteen aqueous PAHs on cork waste at a particle of size 0.25?0.42 mm obtained from the remains of cork strips. The final purpose is to use this natural adsorbent as an alternative to activated carbon in an innovative approach for the removal of this class of toxic compounds, and significantly reduce the regeneration costs of the process. The chemical composition of the selected cork revealed that suberin (38.5 %) and lignin (31.6 %) were the main structural components of the cell wall. The high efficiency of cork as a biosorbent of PAHs is shown by the fact that just over 80 % of adsorption occurred during the first two minutes of contact time. Both Freundlich's and Langmuir's isotherms gave good fits to the sorption process. The highest adsorption affinities were exhibited for pyrene, anthracene, and phenanthrene. Desorption studies indicate a high degree of irreversibility for all PAHs, and especially so in the case of high molecular PAHs. The correlation with KF and low molecular weight PAHs was the most significant. The quantity of cork required to reduce water pollution was estimated to be between 3 and 15 times less than the quantities required in the case of other materials (i.e. aspen wood and leonardite). This study demonstrates for the first time that cork is a potential biosorbent for PAHs and may have relevance in the future treatment of PAH-contaminated waters.
From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)The following values have no corresponding Zotero field: publisher: Taylor & Francis accession-num: 21644164
Keywords: Adsorption; Aromatic; Aromatic: chemistry; biosorbent; Chemical; Chemical: chemistry; Cork waste; Environmental Remediation; Environmental Remediation: methods; Gas Chromatography-Mass Spectrometry; Lignin; Lignin: chemistry; Lipids; Lipids: chemistry; organic pollutants; PAHs; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Solid Phase Microextraction; sorption-desorption; Time Factors; Water Pollutants; water treatment

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Persistent organic pollutants in cork used for production of wine stoppers. - Mazzoleni, V.; Dallagiovanna, L.; Trevisan, M.; Nicelli, M. (Chemosphere, 2005)
Owing to the lipophilic character of some components of cork and the long periods in the open air (during growth and barks storage), there is a risk of the cork becoming environmentally polluted. Moreover, cork stoppers are in contact with wines for periods ranging from a few months to several years; so they must maintain high levels of hygiene. The present work aims to investigate the level of PCBs, organochlorine pesticides, and PAHs in cork from different countries, used for the manufacturing of one-piece wine stoppers. Samples of cork were analysed using a multi-residue method. PCBs were not detected in all the samples; only a few samples contained detectable amounts of DDE; phenanthrene and anthracene were found in all the samples and fluoranthene in fewer cases. It was not possible to find a significant correlation between POPs concentration and origin of cork. Globally, the detected amounts are consistent with values found in foods, so the investigated cork show a suitable hygienic quality.
The following values have no corresponding Zotero field: accession-num: 15694474
Keywords: Cork; Organochlorine pesticides; PAHs; PCBs

Persistent organic pollutants in cork used for production of wine stoppers. - Mazzoleni, V; Dallagiovanna, L; Trevisan, M; Nicelli, M (Chemosphere, 2005)
Owing to the lipophilic character of some components of cork and the long periods in the open air (during growth and barks storage), there is a risk of the cork becoming environmentally polluted. Moreover, cork stoppers are in contact with wines for periods ranging from a few months to several years; so they must maintain high levels of hygiene. The present work aims to investigate the level of PCBs, organochlorine pesticides, and PAHs in cork from different countries, used for the manufacturing of one-piece wine stoppers. Samples of cork were analysed using a multi-residue method. PCBs were not detected in all the samples; only a few samples contained detectable amounts of DDE; phenanthrene and anthracene were found in all the samples and fluoranthene in fewer cases. It was not possible to find a significant correlation between POPs concentration and origin of cork. Globally, the detected amounts are consistent with values found in foods, so the investigated cork show a suitable hygienic quality.
Keywords: Cork; Organochlorine pesticides; PAHs; PCBs